Participatory Action Research as a Framework for Transdisciplinary Collaboration: A Pilot Study on Healthy, Sustainable, Low‐Income Housing in Delhi, India. Issue 4 (13th November 2018) - Nix, Emily; Paulose, Jacob; Shrubsole, Clive; Altamirano‐Medina, Hector; Belesova, Kristine; Davies, Michael; Khosla, Renu; Wilkinson, Paul
Abstract: To tackle global challenges, research collaborations need to integrate multiple disciplinary perspectives and connect with local practices to find solutions that are sustainable and impactful. This paper discusses how participatory action research (PAR) is used as a framework for transdisciplinary collaboration to integrate different disciplines and identify healthy and sustainable housing solutions appropriate for local development practices and policy. By analyzing a transdisciplinary research collaboration investigating housing interventions for low‐income settlements in Delhi, reflections and recommendations are provided for other projects wishing to use a similar methodology. It is found that the PAR framework has successfully guided the integration of contrasting methods and improved the impact of research outcomes, resulting in the emergence of new shared practices. However, it proves to be challenging and requires heightened communication and engagement to achieve understanding between all disciplines and practices. It is recommended that focus is given to developing relationships and effective communication channels and that time should be preallocated for reflection. The work provides insights for integrating academic disciplines, the community, and relevant stakeholders in the cocreation of evidence that is paramount to formulate effective solutions to global challenges. Abstract : Integrating academic disciplines, the community, and relevant stakeholders in the cocreation of evidence is vital to formulate effective solutions for global challenges. Guidance is provided for researchers seeking to use a participatory and transdiscplinary approach by analyzing a research collaboration that employs a participatory action research framework to investigate housing interventions for low‐income settlements in Delhi.